Blueprint Modul Digital Teknik Dasar Bermain Matakuliah TP. Pembelajaran Tenis Lapangan dalam Hybrid Learning - Gunarto, Peby (SPRINTER: Jurnal Ilmu Olahraga, 2024)
The creation of digital teaching materials for basic tennis playing techniques in hybrid learning is a must for lecturers in charge of the TP course. Tennis Court Learning. The purpose of this study was to obtain a design concept for the development of a digital module for the TP course. Tennis Court Learning. The method used was a focus group discussion (FGD) with students and the coordinator of the Physical Education, Health and Recreation study program, from this method data was obtained in the form of a story board for the design of digital teaching materials as a basis for developing the next stage. Digital teaching materials can provide support for the learning process individually or in collaboration with friends without knowing the time limit and the progress of learning. TP. Tennis Court Learning material on basic tennis playing techniques by creating a module cover that combines new colors, demonstrations of holding a racket, stages of techniques, and common mistakes often made by beginners. The color of the module template that appears on each page is also a new color.